Fault resilience in sensor networks: Distributed node-disjoint multi-path multi-sink forwarding. (November 2015) - Chakraborty, Suchetana; Chakraborty, Sandip; Nandi, Sukumar; Karmakar, Sushanta
Abstract: Sensor network deployed for the critical infrastructure monitoring requires high degree of reliability in sensory data gathering, in spite of arbitrary node or sink failures. This paper proposes a robust data gathering scheme specially designed to provide guaranteed delivery of the sensory data for applications on the critical infrastructure monitoring. Redundancy in a sensor network, in terms of both the number of deployed sensors and the amount of duplicate data delivery, is explored to design an effective protocol that ensures the reliable data delivery while assuring the timeliness, connectivity and the sensing coverage. A set of active sensors is selected from all the sensors deployed, based on the network connectivity and the sensing coverage criteria that participates in the data forwarding process. Rest of the sensors go to the sleep state, and act as a replacement on the failure of an active sensor. The proposed protocol aims to find out multiple node-disjoint paths to multiple sinks, so that the loss of connectivity in one path due to node failure does not disrupt application services. The effectiveness of the proposed scheme has been analyzed using simulation results, and compared with other protocols proposed in the literature for reliable data delivery.